Embodying Peripheries - Forte, Giuseppina; Hwa, Kuan (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This book combines approaches from the design disciplines, humanities, and social sciences to foster interdisciplinary engagement across geographies around the identities embodied in and of peripheries. Peripheral communities bear human faces and names, necessitating specific modes of inquiry and commitments that prioritize lived human experience and cultural expression. Hence, the peripheries of this book are a question, not a given, the answers to which are contingent forms assembled around embodied identities. Peripheries are urban fringes, periphery countries in the modern world-system, Indigenous lands, occupied territories, or the peripheries of authoritative knowledge, among others. No form can exist outside historical relations of power enacted through knowledge, political structures, laws, and regulations.